Potensi Tanaman Obat Terhadap Epitelisasi dalam Penyembuhan Luka Bakar - Suratmini, Putu Ayu; Wardani, I Gusti Agung Ayu Kusuma; Suena, Ni Made Dharma Shantini (Usadha, 2021)
Burns are damage to the skin caused by fire, hot water, electricity, chemicals and radiation. In wound healing, epithelialization plays an important role in the regeneration of epithelial cells. Increased epithelialization causes wounds to close faster and improves the wound healing process. Treatment of burns must be done properly so that the healing process is not disturbed and infection is avoided. However, treating wounds using conventional drugs requires relatively more expensive costs, so alternatives are needed in treating burns by utilizing medicinal plants. This article review aims to determine the potential of medicinal plants for epithelialization in healing burns. The method used in this article is a literature review of scientific research journals that have been published from 2011 to July 10, 2021 in the Google Scholar, PubMed, Sciencedirect and Plos One databases. 11 Indonesian and English scientific research journals were obtained, then these journals were screened. From the results of the review of the articles, it was found that several medicinal plants have the potential for epithelialization in healing burns, including: Ampelopsis japonica, Ananas comosus, Anredera cordifolia, Bixa orellana, Carica papaya, Carissa spinarum, Curcuma longa, Phyllanthus niruri, Poincianella pluviosa, Rhaphidophora pinnata, and Solanum tuberosum.